PENDEKATAN SAINTIFIK DAN PENILAIAN AUTENTIK UNTUK MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Dika Setiawan (Universitas Muhammadiyah Ponorogo, 2017)
Research objectives for describing an application of scientific learning approach on Islamic religious education lessons in Elementary School Muhammadiyah Sapen and application of authentic assessment in the subject Islamic studies, as well as the description do approach to scientific learning and assessment can improve the quality of learning of authentic Islamic education in Muhammadiyah Sapen elementary school. The type of research used is evaluative research program with research approaches to mixed methods (qualitative and quantitative). The technique of collecting data through in-depth interviews and documentation. The results of these research findings are as follows (1) On scientific learning administration device owned by the teachers have not been adequate because of the completeness of an administration owned teachers still refers to KTSP curriculum. Padaproses PAI has not fully observed the teaching steps in scientific learning, which includes observations, asking questions, trying, rational and communicate. (2) on the assessment process, authentic teachers still experience difficulties especially since the high and complexity of curriculum assessment of 2013. (3) the quality of learning Occurs in the primary PIE Muhammadiyah Sapen experience increased, ranging from improved process i.e. business guru PAI SD Muhammadiyah Sapen to creatively make administration curriculum tailored to 2013 and the end result be the values obtained showed an increase in students from semester to semester II